2006
DOI: 10.1093/toxsci/kfl145
|View full text |Cite
|
Sign up to set email alerts
|

Gasoline Exhaust Emissions Induce Vascular Remodeling Pathways Involved in Atherosclerosis

Abstract: Epidemiological evidence indicates that environmental air pollutants are positively associated with the development of chronic vascular disease; however, the mechanisms involved have not been fully elucidated. In the present study we examined molecular pathways associated with chronic vascular disease in atherosclerosis-prone apolipoprotein E-deficient (ApoE(-/-)) mice, including markers of vascular remodeling and oxidative stress, in response to exposure to the ubiquitous environmental pollutant, gasoline eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
87
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 34 publications
12
87
0
Order By: Relevance
“…This is in line with in vivo studies, which report toxic effects of gasoline exhaust, particularly also after filtration with a GPF [44,45]. Epidemiological studies on the other hand could not find or find only weak associations between gasoline engine exhaust and e.g.…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with in vivo studies, which report toxic effects of gasoline exhaust, particularly also after filtration with a GPF [44,45]. Epidemiological studies on the other hand could not find or find only weak associations between gasoline engine exhaust and e.g.…”
Section: Discussionsupporting
confidence: 87%
“…Sun et al (27,28) used an apolipoprotein E knockout (ApoE -/-) mouse model to show that long-term exposure to low concentrations of PM 2.5 (particles smaller than 2.5 µm in diameter) altered vasomotor tone, and increased tissue-factor expression, vascular inflammation and atherosclerotic burden in these animals. Research at the Lovelace Respiratory Research Institute (New Mexico, USA) in ApoE -/-mice has shown vascular remodelling and altered atherosclerotic plaque composition following PM 10 exposure and diesel emission exposure (29)(30)(31). The present study was designed to determine whether and how PM 10 exposure affected the architecture of existing atherosclerotic plaques and to determine whether the observed ultrastructure was consistent with the characteristics of a more vulnerable atherosclerotic plaque.…”
Section: Méthodologie : Les Lapins Whlh (N=8) Exposés à 5 Mg De Partimentioning
confidence: 93%
“…Several studies in the ApoE -/-mouse have shown the transcriptional upregulation of factors associated with vascular remodelling including MMP-3, -7 and -9 following PM 10 exposure (29,30), and MMP-9 following diesel exhaust exposure (31). Future work testing for colocalization of these MMPs with migrating foam cells in the WHHL rabbit model would be of interest.…”
Section: Figure 9) a Protruding Leukocyte Is A Macrophage-derived Foamentioning
confidence: 98%
“…For example, ApoE⁻/⁻ mice were exposed by inhalation 6 hours a day for 50 consecutive days to multiple dilutions of diesel or gasoline exhaust, woodsmoke, or simulated downwind coal emissions. From Lund et al (2007), as well as a meta-analysis by Seilkop et al (2012), it can be concluded that filtration of particles has little effect on responses − that is, particulate components ranked third to seventh in predictive importance for the eight response variables. This suggests that not only the particles, but certainly also the gaseous fraction of engine exhaust is related to adverse health effects.…”
Section: Clinical and Toxicological Studiesmentioning
confidence: 99%